Manoscritti ebraici nell’abbazia di Montecassino - Beit-Arié, Malachi (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2013)
Il contributo presenta, in forma leggermente diversa, due codici ebraici di origine iberica e due frammenti, poco noti, in parte già descritti in M. Beit-Arié, “A Discovery of Hebrew Manuscripts in the Monastery of Montecassino”, Report of the Oxford Centre for Hebrew and Jewish Studies (2007-8) 77-80. Il primo, il Ms. 503, contiene un Pentateuco vocalizzato, con Haftarot e Megillot, databile al 1300 circa. Il secondo codice, il Ms. 510, è una compilazione di testi matematici formata in realtà da due manoscritti diversi: il primo con gli Elementi di Euclide e il Trattato sulla sfera di Teodosio; mentre il secondo contiene il Sefer ha-Middot attribuito ad Avraham ibn Ezra. Per quanto riguarda i due frammenti, il primo, palinsesto, proviene da un codice delle Hilḵôṯ di Isaac b. Jacob Alfasi; il secondo frammento presenta una porzione dei Libri dei Re, ed è stato tratto da un codice prodotto probabilmente in Spagna verso il 1200. Hebrew Manuscripts in the Montecassino Abbey During a visit at the library of Montecassino Abbey, among the collection of Latin manuscripts two Hebrew manuscripts and two reused Hebrew fragments were recovered. The manuscripts seemed unknown to the Institute of Microfilmed Hebrew Manuscripts. Both the main manuscripts are of Spanish origin. One codex, Ms. 503, contains a vocalized Pentateuch, with Haftarot and the five Megillot. It was written on 262 parchment folios in a large quarto format and written in a square Sefardic type of script from c. 1300. The other codex, Ms. 510, is a mathematical compilation including two different manuscripts: the first one including Euclid’s Elements and Theodosius’ Spherics (ff. 1-132); the second one containing the Sefer ha-Middot attributed to Abraham Ibn Ezra (ff. 133-144). As for the two fragments, the first one is formed by two conjugated folios (a palimpsest bifolium) from a manuscript of Hilḵôṯ of Isaac b. Jacob Alfasi; the other one is a folio bearing part of the book of Kings, formerly belonging to a very large Hebrew codex produced in Spain, probably around 1200.